Pengaruh Pendekatan Scientific Berbasis Realistic Mathematics Education (RME) Terhadap Prestasi Belajar Matematika Ditinjau Dari Kreativitas Siswa Kelas VII SMP Muhammadiyah 1 Kartasura Tahun Ajaran 2014/2015 - Nur Azizah, Dessy Ilma Berliana; , Nining Setyaningsih, Dra. M.Si (2015)
This study aims to analyze and examine: (1) the influence of scientific approach based Realistic Mathematics Education (RME) on mathematics achievement, (2) the influence of creativity on mathematics achievement, and (3) the interaction between the scientific approach based Realistic Mathematics Education (RME ) on the mathematics achievement of students in terms of creativity. The population in this study were all students of SMP Muhammadiyah 1 Kartasura 7th even semester academic year 2014/2015. The sample used in this study were two classes of 7th A class as an experimental class scientific subject-based learning approach Realistic Mathematics Education and 7th C class as the class that is subject to the control with conventional approaches. The sampling technique using cluster random sampling. Data collection methods used the method of questionnaire, test methods and documentation. Data were analyzed using two-way analysis of variance test with different cells, which previously performed analysis prerequisite test is test Lilliefors normality and homogeneity test method with the Bartlett method. From the results of data analysis with significance level of 5% was obtained results: (1) scientific approach based Realistic Mathematics Education (RME) has no effect on mathematics achievement with FA = 2.23 < Ftab = 4.06, (2) Creativity effect on mathematics learning achievement with FB = 25.5> Ftab = 3.21, and (3) There is no interaction between the scientific approach based Realistic Mathematics Education (RME) on mathematics achievement of students in terms of creativity with FAB = 0.58 > Ftab = 3.21.